The evolutionary history of Biston suppressaria (Guenée) (Lepidoptera: Geometridae) related to complex topography and geological history. (3rd May 2016) - CHENG, RUI; JIANG, NAN; XUE, DAYONG; LI, XINXIN; BAN, XIAOSHUANG; HAN, HONGXIANG
Abstract: The Mountains of Southwest China (MSC) – the most important mountain system in East Asia – creates physical barriers to migration and isolates organisms in different regions. In this study, we explored the genetic structure and phylogeography of Biston suppressaria, a moth species widely distributed in MSC and south China, based on three mtDNA and three ncDNA loci. MtDNA revealed high genetic differentiation among the geographical populations and divided B. suppressaria into five phylogroups (A–E). With the exception of phylogroups B and E which are sympatric, the other three phylogroups have their own distinct distribution areas. Four population differentiations occurred, and the divergence time was consistent with the three phases of the Qinghai–Tibet Movement and Kunhuang Movement, respectively. In contrast, ncDNA did not reveal any phylogeographical structure. Incomplete lineage sorting is considered the most plausible cause of the discordance between mtDNA and ncDNA genes, after excluding secondary admixture and Wolbachia infection. A complex combination of topography and geological movements of south China and MSC contributes to the complex evolutionary history of B. suppressaria .